A Study of Heating Effect on the Structural and Optical Absorbance of Olive Oil - Ali, Mays K; Essa, Mohammed Sh.; Chiad, Bahaa T. (Iraqi Journal of Science, 2018)
In this study, the number of times of heating of olive oil was studied. For the different refineries, the study was conducted using a temperature of 300K and for several times to determine the validity of the olive oil which is used for frying purposes after it was used for more than once times. It was found that there were significant changes in the behavior of the photophysical behavior like absorption and emission; there are changes in the nature and composition of the olive oil molecule, which makes it not useful for human use. The number of heating times was ten. The heating times also showed significant changes in the nature of the oil, such as color, taste, density, and smell.